Being the Unbook, Being the Change: The Transformative Power of Open Sources - Elizabeth D. Woodworth (Journal of the Assembly for Expanded Perspectives on Learning, 2011)
A director of composition tests and advocates “open education sources” for the development of curricula and programs.